Aetiology and epidemiology of grapevine anthracnose - Santos, Ricardo Feliciano dos (2017)
Grapevine anthracnose is an important disease, responsible for severe yield losses in humid regions around the world. This study aimed to: i: identify the causal agents of grapevine anthracnose in Brazil; ii: characterize Elsinoë ampelina isolates from Brazil and Australia by means of phylogenetic analyses, morphological features and pathogenicity tests; iii: develop an efficient method for conidial production of E. ampelina; iv: develop and validate a standard area diagram set (SADs) for assessing anthracnose severity on grapevine leaves; and v: study the temporal and spatial progression of anthracnose in a Brazilian vineyard. To identify the causal agents of the disease, leaves, stems and berries with anthracnose symptoms were collected from 38 vineyards in southern and southeastern Brazil and 39 E. ampelina and 13 Colletotrichum spp. isolates were obtained. For E. ampelina isolates, the internal transcribed spacer (ITS), histone H3 (HIS3) and elongation factor 1-α (TEF) sequences were analysed. HIS3 was the most informative region with 55 polymorphic sites. Seven Colletotrichum species were identified: C. siamense, C. gloeosporioides, C. fructicola, C. viniferum, C. nymphaeae, C. truncatum and C. cliviae. In pathogenicity tests, only E. ampelina isolates caused anthracnose symptoms on Vitis vinifera \'Moscato Giallo\' and Vitis labrusca \'Niagara Rosada\'. To characterize E. ampelina from Brazil and Australia, 35 isolates were analysed. ITS and TEF sequences of all isolates were monomorphic. The haplotype network generated from HIS3 dataset showed four distinct haplotypes. High genetic variability was observed in two Brazilian isolates, haplotype EA4, which may have lost the intron region during species evolution. Colonies showed variable coloration, wrinkled texture, absence of spores and slow growth. Brazilian isolates produced conidia larger than conidia from Australian isolates. To induce the conidial production, mycelial fragments were shake-incubated in rainwater and distilled water for 7 days. Isolates produced different concentrations of conidia and the conidial germination was more than 88.5%. In infectivity tests, conidia caused typical anthracnose symptoms on leaves. The SADs developed comprises six true colour diagrams with severity ranging from 1.1 to 27.4%. The use of the SADs improved the accuracy, precision, agreement and inter-rater reliability of the estimates conducted by 12 raters. The temporal and spatial dynamics of anthracnose was carried out in a \'Niagara Rosada\' vineyard in 2014 and 2015. The incidence of vines with diseased leaves, stems and berries and the severity disease on leaves were recorded. Anthracnose symptoms occurred rapidly after bud break and ontogenic resistance was observed for all organs assessed. The monomolecular model showed the best fit to the incidence progress. Temporal analyses suggest that the progress of anthracnose incidence and severity over time is governed mainly by the primary inoculum due to age-related resistance of the vine organs. Spatial analyses showed a predominantly random spatial pattern of diseased vines. In conclusion, this thesis presents a more in-depth understanding of the aetiology and epidemiology of an important grapevine disease.